Identification of fluency and word‐finding difficulty in samples of children with diverse language backgrounds. Issue 5 (30th December 2016) - Howell, Peter; Tang, Kevin; Tuomainen, Outi; Chan, Sin Kan; Beltran, Kirsten; Mirawdeli, Avin; Harris, John
Abstract: Background: Stuttering and word‐finding difficulty (WFD) are two types of communication difficulty that occur frequently in children who learn English as an additional language (EAL), as well as those who only speak English. The two disorders require different, specific forms of intervention. Prior research has described the symptoms of each type of difficulty. This paper describes the development of a non‐word repetition test (UNWR), applicable across languages, that was validated by comparing groups of children identified by their speech and language symptoms as having either stuttering or WFD. Aims: To evaluate whether non‐word repetition scores using the UNWR test distinguished between children who stutter and those who have a WFD, irrespective of the children's first language. Methods & Procedures: UNWR was administered to ninety‐six 4–5‐year‐old children attending UK schools (20.83% of whom had EAL). The children's speech samples in English were assessed for symptoms of stuttering and WFD. UNWR scores were calculated. Outcomes & Results: Regression models were fitted to establish whether language group (English only/EAL) and symptoms of (1) stuttering and (2) WFD predicted UNWR scores. Stuttering symptoms predicted UNWR, whereas WFD did not. These two findings suggest that UNWR scores dissociate stuttering from WFD. There were no differences between monolingual English‐speakers and children who had EAL. Conclusions & Implications: UNWR scores distinguish between stuttering and WFD irrespective of language(s) spoken, allowing future evaluation of a range of languages in clinics or schools.